Management of sarcopenia in patients with rheumatoid arthritis. Issue 3 (20th August 2022) - Torii, Mie; Itaya, Takahiro; Minamino, Hiroto; Katsushima, Masao; Fujita, Yoshihito; Tanaka, Hiroki; Oshima, Yohei; Watanabe, Ryu; Ito, Hiromu; Arai, Hidenori; Hashimoto, Motomu
ABSTRACT: This review summarizes the evidence for the management of sarcopenia in patients with rheumatoid arthritis (RA) in terms of drugs, exercise, and nutrition. Sarcopenia is a decrease in skeletal muscle mass and muscle strength or physical function. The prevalence of sarcopenia in patients with RA is higher than that in the general population. The treatment and management of sarcopenia in patients with RA are clinically important for long-term prognosis. One of the mechanisms of muscle metabolism is the pro-inflammatory cytokine pathway, which involves tumour necrosis factor α and interleukin-6, and is a common pathway in the pathogenesis of RA. Thus, tumour necrosis factor α and interleukin-6 inhibitors may play a potential role in controlling sarcopenia. In exercise therapy, a combination of moderate resistance and aerobic exercise may be effective in improving muscle strength, muscle mass, and physical function; however, intense exercise may exacerbate the inflammatory response in RA. Regarding nutrition, protein intake is generally considered beneficial, but other nutrients such as vitamin D and carotenoids have also been studied. Overall, there remains a lack of concrete evidence on sarcopenia treatment and management in patients with RA from any perspective; more longitudinal and intervention studies are needed in the future.